Hypoglycemic effect and toxicity of the dry extract of Eugenia biflora (L.) DC. leaves. (15th July 2022) - Oliveira, Edinilze S.C.; Acho, Leonard D.R.; da Silva, Bárbara Janaína P.; Morales-Gamba, Ruben Dario; Pontes, Flávia L.D.; do Rosário, Alessandro S.; Bezerra, Jaqueline de A.; Campos, Francinete R.; Barcellos, José Fernando M.; Lima, Emerson S.; Machado, Marcos B.
Abstract: Ethnopharmacological relevance: The leaves of Eugenia biflora (Myrtaceae) are traditionally used by Amazonian populations for the control of diabetes. However, their chemical composition has not yet been described and pharmacological evidence has not been reported. Objective: This study aimed to identify the chemical constituents and evaluate the hypoglycemic and toxic effect of the dry extract of the E. biflora leaves (DEEB). Materials and methods: DEEB, obtained by infusion, was analyzed using LC-HRMS and NMR, whose the catechin flavonoid was quantified using NMR. The antidiabetic effect of DEEB was evaluated according to its inhibition of the enzymes α-amylase and α-glucosidase, as well as the content of total phenols, free radical scavengingand antiglycation activities, and its in vitro cell viability. Oral maltose tolerance and chronic multiple dose tests (28 days) in streptozotocin-induced diabetic mice (STZ) were performed. The hypoglycemic effect and toxicity of this extract were evaluated in the multiple dose assay. Biochemical parameters, hemolysis, and levels of the thiobarbituric acid reactive species in the liver were investigated and histopathological analyses of the kidneys and liver were performed. Results: Eight phenolic compounds were identified, with catechin (15.5 ± 1.7 mg g−1) being the majority compound and a possible chemical marker of DEEB. The extract showed inhibition activity of the enzyme α-glucosidase. Chronic administration of DEEB (50 mg/kg of body weight) reduced glucose levels in diabetic animals, similar to acarbose; however, DEEB (100 and 200 mg/kg bw) caused premature death of mice by D22 of the treatment. Our data indicate that one of the mechanisms of toxicity in DEEB may be related to the aggravation of oxidative stress in the liver. This histopathological study indicated that DEEB failed to minimize the progression of the toxicity of diabetes caused by STZ. Conclusions: This study demonstrated the hypoglycemic potential of E. biflora leaves. However, the prolonged use of this tea can be harmful to its users due to its considerable toxicity, which needs to be better investigated. Graphical abstract: Image 1 Highlights: Eight phenolic compounds were identified using HRMS and NMR of E. biflora leaves. The flavonoid catechin was quantified in Eugenia biflora leaf extract using qNMR. The dry extract of E. biflora inhibited the α-glucosidase enzyme in vitro. E. biflora leaf extract showed a hypoglycemic effect in diabetes induced mice. E. biflora leaf extract caused side effects and mortality in diabetic mice.